Does Shamanism Have a History? With Attention to Early Chinese Shamanism - Michael, Thomas (Numen, 2017)
The article examines various options that scholars have explored in their efforts to construct a history of shamanism. Recognizing Eliade’s promise that such a history lies in the near future, the article then explores the important ways in which this has been undertaken. It specifies four such ways: with prehistoric rock art, the origins of cultural myths, memory studies, and movements of cultural resistance. Ultimately resisting each of these four options while paying particular attention to the case of early Chinese shamanism, its concluding sections recognize the work of Mircea Eliade and Roberte Hamayon as providing two alternative pathways that might lead into possible constructions of this history, and it then attempts to locate a third way between them.